Relative Importance for Lincoln’s Sparrow (Melospiza lincolnii) Occupancy of Vegetation Type versus Noise Caused by Industrial Development - Sánchez, Natalie V.; Sandoval, Luis; Hedley, Richard W.; St. Clair, Colleen C.; Bayne, Erin M. (Frontiers in Ecology and Evolution, 2022)
Anthropogenic noise can create an acoustic environment detrimental for animals that communicate using acoustic cues. However, most studies of noise and wildlife come from traffic noise in cities. Less is known about the effects of noise created by industry in natural areas. Songbirds far from cities, but influenced by industry, could be affected by noise, but also are likely to be impacted by changes in vegetation conditions related to development. We described the importance of industrial noise (from facilities and transportation) on occupancy of Lincoln’s Sparrow (Melospiza lincolnii) relative to habitat change caused by vegetation alteration and edge effects. Lincoln’s Sparrows naturally breed in varying seral stages and types of boreal forest. To test the influence of industrial noise, we selected three areas in Northern Alberta with high, medium, and low levels of industrial development and varying road density. At each area, we deployed a systematic arrangement of autonomous recording units (280 units in total, separated by 600 m) for 3 consecutive days. To measure noise, we developed a method that used the relative noise values extracted from the recordings of 8 frequency-octave bands. We obtained 3 noise measurements: noise with high energy in the low part of the spectrum (mean 0.5 – 1 kHz), masking level noise (mean 2 – 8 kHz), and noise in all frequency octave bands (mean 0.5 – 16 kHz). Proportion of chronic noise sources explained the highest variation of noise in the environment, and less by traffic noise. We found Lincoln’s Sparrow had a higher occupancy in areas with higher proportion of industrial disturbances, shrubs and grass, and decreased in noisy areas. Masking level noise had a negative effect on Lincoln’s Sparrow occupancy in areas with industrial disturbances, relative to areas with similar changes in vegetation structure, but no noise. Masking noise could indicate limitation in communication as noise increases. Our study amplifies the findings of others that future research should consider not only anthropogenic changes to vegetation in human-altered landscapes, but also human-caused changes to acoustic environments.